2017
DOI: 10.15273/pnsis.v49i1.6979
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of the terrestrial green alga, Prasiola crispa (Trebouxiophyceae), and associated Herring Gulls on Brier Island, Nova Scotia

Abstract: The local distribution of Prasiola crispa is reported for the first time in Nova Scotia. It was common on emergent basalt outcrops in a coastal wetland on the Bay of Fundy shores of Brier Island. The alga was present on 19 of 102 basalt outcrops in one of the breeding colonies of the Herring Gull, Larus argentatus, and was only associated with basalt outcrops with gull feces. Patches of P. crispa were typically associated with the north facing slopes of the rock or were present in depressions or parts of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Cellular and ultrastructural characters and molecular analysis support the idea that Prasiolales is a monophyletic well-defi ned order and has a relationship with the Trebouxiophyceae, Chlorophyta (Garbary & Hill, 2017;Heesch et al, 2016;Moniz et al, 2012;Pang et al, 2021). A total of 37 species have been reported in the green algal genus Prasiola (Guiry & Guiry, 2022), with as many as 14 documented as freshwater organisms (Moniz et al, 2012), and 11 of which are reported in Asia (Kim et al, 2015;Pang et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Cellular and ultrastructural characters and molecular analysis support the idea that Prasiolales is a monophyletic well-defi ned order and has a relationship with the Trebouxiophyceae, Chlorophyta (Garbary & Hill, 2017;Heesch et al, 2016;Moniz et al, 2012;Pang et al, 2021). A total of 37 species have been reported in the green algal genus Prasiola (Guiry & Guiry, 2022), with as many as 14 documented as freshwater organisms (Moniz et al, 2012), and 11 of which are reported in Asia (Kim et al, 2015;Pang et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
“…Parasiola fl uviatilis (Sommerfelt) Areschoug ex Lagerstedt is characterized from other freshwater species by its linear thallus and is reported from glacial-fed streams across the northern Arctic between 70-80°N (Hamilton & Edlund, 1994;Kováčik & Pereira, 2001;Garbary & Hill, 2017). In Europe, it is reported in the Alps (Dalla Torre & Sarnthein, 1901 as cited in Rott et al, 2006) and Tatra mountains (Kawecka, 1990); in North America, P. fl uviatilis has been observed from the Bald Mountains in British Columbia (Taylor, 1928) and in South America recorded from the Andes, Bolivia (McClintic et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Further physiological and ecological studies were carried out on Palmaria palmata (e.g. Garbary et al 2012), Prasiola stipitata (Kang et al 2014); Ascophyllum nodosum and Vertebrata lanosa (Garbary 2017a); and Prasiola crispa (Garbary and Hill 2017). There are complementary floristic studies from the western side of the Bay of Fundy in both Canada and USA.…”
Section: Introductionmentioning
confidence: 99%